2016
DOI: 10.1007/s10519-015-9777-8
|View full text |Cite
|
Sign up to set email alerts
|

Tspyl2 Loss-of-Function Causes Neurodevelopmental Brain and Behavior Abnormalities in Mice

Abstract: Testis specific protein, Y-encoded-like 2 (TSPYL2) regulates the expression of genes encoding glutamate receptors. Glutamate pathology is implicated in neurodevelopmental conditions such as autism spectrum disorder, attention deficit hyperactivity disorder (ADHD) and schizophrenia. In line with this, a microduplication incorporating the TSPYL2 locus has been reported in people with ADHD. However, the role of Tspyl2 remains unclear. Therefore here we used a Tspyl2 loss-of-function mouse model to directly examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…TSPX interacts with calcium/calmodulin-dependent serine protein kinase (CASK) and modulates the Tbr-1 regulation of the N-methyl-D-aspartate (NMDA) receptor subunit and other neural genes 19353637. Loss-of-function mutation of Tspx in mice results in neurodevelopmental and behavioral abnormalities,3839 suggesting that TSPX could be an essential gene for neurodevelopment and synaptic functions. TSPX has been demonstrated to be an essential component of the RE1-silencing transcription factor/neuron-restrictive silencer factor (REST/NRSF) transcriptional repressor complex, which regulates numerous neuronal genes and could also serve as tumor suppressor for various cancers 40.…”
Section: The Normal Functions Of Tspy and Tspx Genesmentioning
confidence: 99%
“…TSPX interacts with calcium/calmodulin-dependent serine protein kinase (CASK) and modulates the Tbr-1 regulation of the N-methyl-D-aspartate (NMDA) receptor subunit and other neural genes 19353637. Loss-of-function mutation of Tspx in mice results in neurodevelopmental and behavioral abnormalities,3839 suggesting that TSPX could be an essential gene for neurodevelopment and synaptic functions. TSPX has been demonstrated to be an essential component of the RE1-silencing transcription factor/neuron-restrictive silencer factor (REST/NRSF) transcriptional repressor complex, which regulates numerous neuronal genes and could also serve as tumor suppressor for various cancers 40.…”
Section: The Normal Functions Of Tspy and Tspx Genesmentioning
confidence: 99%
“…Collectively, the data strongly suggest that TSPYL2 and EZH2 dynamically regulated the expression of important synaptic genes in hippocampal neurons. Defects in the fine tuning of gene expression can contribute to the phenotype of our Tspyl2 knockout mice reported previously [ 9 , 10 ]. For example, Egr3 is important for hippocampal long-term potentiation and fear conditioning [ 50 ].…”
Section: Discussionmentioning
confidence: 96%
“…Targeted mutation of Nap1l2 results in abnormal proliferation of neural progenitor cells and the phenotype resembles spina bifida [ 5 ]. By contrast, targeted mutation of Tspyl2 results in impaired hippocampal long term potentiation and behavioral phenotypes [ 6 , 9 , 10 ]. Our group has shown that TSPYL2 directly regulates the transcription of genes for NMDA receptor subunits 2A ( Grin2a ) and 2B ( Grin2b ) in mice [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate pathology is involved in neurodevelopmental conditions, and CDA1 regulates the expression of genes encoding glutamate receptors. CDA1 KO mice may have neurodevelopmental and behavioral abnormalities due to the disruption of glutamate signaling, mainly manifested as sensorimotor gating impairment, mild hyperactivity, and hypersensitivity to the dopamine agonist amphetamine [ 61 ]. Subsequently, the study found that compared with wild type littermates, the expression of H3K27me3 (a key histone modification important for brain development and neuronal function) in the hippocampus of CDA1 KO mice was upregulated.…”
Section: Function Of Cda1mentioning
confidence: 99%